Keniscayaan Memahami Fikih Muamalat bagi Wirausaha - Zuhrinal M Nawawi (Journal of Islamic Social Finance Management, 2021)
Islam as a universal religion, teaches all aspects of the lives of its adherents such as matters of worship, morals, including procedures in everyday life which we often call muamalat. For Muslim entrepreneurs, it is a necessity to know and understand religious law in business, especially fiqh muamalah. So that they understand about business and entrepreneurship; and understand the concept of fiqh muamalah, its scope in contemporary business, and the rules of fiqh that are appropriate for contemporary business. Islam emphasizes the importance of developing and upholding an entrepreneurial culture in the life of every Muslim. A Muslim entrepreneur must have basic qualities that encourage him to be a creative and reliable person in running his business or carrying out activities at the company where he works.